Pengaruh Dosis dan Frekuensi Pemberian Pupuk Tunggal (N,P,K) dan Pupuk Majemuk NPK Terhadap N-Total, P-tersedia dan K-dd Padi Sawah (Oryza sativa L.) pada Inceptisols - Siswanto, Shantosa Yudha; Wianggadana, Rangga; Harryanto, Rachmat; Setiawan, Ade; Sonjaya Sule, Marenda Ishak (Soilrens, 2024)
The study was conducted to determine the effects of dosage and frequency of applying single fertilizers (N,P, K) and compound NPK fertilizers on total nitrogen (N-total) using lowland rice (Oryza sativa L.) grownin Inceptisols. The research was carried out in rice fields located in Ciparay, Jelekong Subdistrict, BaleendahDistrict, Bandung Regency. A Randomized Complete Block Design (RCBD) was employed, consisting of seventreatments with three replications: (1) Control, (2) Single NPK fertilizer (grade 123,75-36-50), Frequency3, (3) Compound NPK Pelangi fertilizer (grade 80-40-40), Frequency 3, (4) Single NPK fertilizer (grade 8040-40),Frequency 3, (5) Single NPK fertilizer (grade 123,75-36-50), Frequency 2, (6) Compound NPKPelangi fertilizer (grade 80-40-40), Frequency 2, and (7) Single NPK fertilizer (grade 80-40-40), Frequency2. The results indicated that, in general, fertilization applied twice yielded the highest N-total values.Meanwhile, fertilization applied three times resulted in higher available phosphorus (P-available) levels.However, differences in fertilization treatments did not significantly affect exchangeable potassium (K) inInceptisols.